TAX SYSTEMS OF COUNTRIES WITH TRANSITION ECONOMIES (British Journal of Global Ecology and Sustainable Development, 2026)
This article examines the formation and development features of tax systems in countries with transition economies. The study identifies the main criteria for classifying transition economies and analyzes the role of tax policy in economic transformation processes as well as the institutional development of tax administration. A comparative analysis of Central and Eastern European countries and CIS states highlights the main directions for modernization of tax systems. The research results provide theoretical and practical conclusions aimed at improving tax policy and ensuring fiscal sustainability in transition economies.